Combined economic emission based resource allocation for electric vehicle enabled microgrids. Issue 6 (30th November 2020) - Umoren, Ifiok Anthony; Shakir, Muhammad Zeeshan
Abstract : As electric vehicles (EVs) are currently under‐utilised, the features of deploying EVs as distributed energy resources (DERs), based on an EV as a service (EVaaS) framework, are exploited and a resource allocation scheme is proposed for optimum association of dispersed EVs with critical load for demand fulfilment in microgrids. The proposed approach is based on a combined economic emission (CEE) optimisation model where both energy costs and carbon emissions are taken into account. The CEE optimisation problem is then formulated as a bi‐objective optimisation problem, considering a number of practical constraints, such as energy demand, cost budget, emission limit and charging station limit. Carbon price is introduced to convert the bi‐objective problem into a single objective function. The authors included EV battery degradation cost to ensure EV owners are not worse off after EVaaS participation. The feasibility of the proposed model is demonstrated in simulation studies. The approach has been extended to evaluate the trade‐off between EVaaS and conventional DERs. Numerical results demonstrate the efficiency of the proposed resource allocation scheme.